France–Japan synthesis concept on sodium-cooled fast reactor review of a joint collaborative work - Rodriguez, Gilles; Varaine, Frédéric; Costes, Laurent; Venard, Christophe; Serre, Frédéric; Chanteclair, Frédéric; Chenaud, Marie-Sophie; Dechelette, Franck; Hourcade, Edouard; Plancq, David; Hamy, Jean-Marie; Dirat, Jean-François; et al. (EPJ Nuclear Sciences & Technologies, 2021)
In the frame of the France-Japan agreement on nuclear collaboration, a bilateral collaboration agreement on nuclear energy was signed on March 21st, 2017, including a topic dedicated to Sodium-cooled Fast Reactor (SFR). This agreement has set the framework to start a bilateral discussion on a joint view of an SFR concept. France (CEA and FRAMATOME) and Japan (JAEA, MHI and MFBR) have carried out these studies from 2017 to 2019. Based on the beginning of the basic design phase of ASTRID project − ASTRID − 600 MWe (ASTRID for Advanced Sodium Technological Reactor for Industrial Demonstration), the two countries performed a common work to examine ways to develop a feasible common design concept, which could be realized both in France and in Japan. The subject was then extended and extrapolated with the ASTRID − 150 MWe data (reduced power reactor and enhanced experimental capabilities) in a second phase of this study. France and Japan first focused on design requirements. Common requirements were identified, as well as differences in the safety approach and the structural design requirements, according to national standards and respective site conditions, in particular considering seismic hazards. The teams developed common Top-Level design Requirements (TLRs) to allow common specification data, then joint design. This collaborative work was carried out through the implementation of twelve France-Japan Working Groups, working jointly. This paper is providing a review of this joint synthesis on Sodium Fast Reactor design concept. It is summarizing the context and objectives, then the definition and approaches of the Top Level Requirements. This paper is then dealing with the major design features: the core design and their related safety aspects, and the nuclear island design. Thus, this paper is providing a comprehensive review of this joint work gathering French and Japan nuclear design teams during two full years.